Mitochondrial respiratory pathways in immature rat heart tissue using different cardioplegic solutions - Mamedov, Arslan; Rumbinaitė, Eglė; Romann, Sebastian W.; Verikas, Dovydas; Jakuška, Povilas; Aitaliyev, Serik; Benetis, Rimantas; Stankevičius, Edgaras (General thoracic and cardiovascular surgery, 2024)
Minor defects in the mitochondrial ATP-generating system and post-cardioplegia oxidative phosphorylation can negatively impact cardiac function in immature hearts. This study aimed to examine the mitochondrial respiratory pathway using three different cardioplegic solutions (Custodiol HTK, St. Thomas, and Del Nido) during moderate (1 h) and long (3 h) ischemic periods.
Gesehen am 17.06.2025